Potential value and research frontiers of virus in neuroinflammation: a bibliometric and visualized analysis - Li, Danyang; Wu, Minghua (Frontiers in Immunology, 2024)
Background Neuroinflammation represents the immune response of the central nervous system to nerve injury, infection, toxin stimulation, or autoimmunity and is implicated in a wide range of neurological disorders. Viruses play a pivotal role as extrinsic biological drivers in neuroinflammation; however, numerous aspects remain unexplored. In this study, we employed bibliometric analysis to assess the current status of viral research in neuroinflammation and anticipate future research directions and emerging trends. Methods Conduct a comprehensive search for scholarly publications within the Web of Science Core Collection database, with search terms on neuroinflammation and virus. Apply Microsoft Excel Office, Hiplot, R (version 4.3.1), VOSviewer (version 1.6.20) and CiteSpace (6.2.R6, advanced) software for the bibliometric analysis and visualization. Results A total of 4230 articles and reviews on virus and neuroinflammation were identified, demonstrating a consistent upward trend over time. The United States was the country that contributed the most publications. Approximately 22274 authors from 4474 institutions contributed to the research. Johns Hopkins University leads with the highest number of publications and citations. The top three authors with the most published articles on this field are Power, C., Lane, T. E., and Buch, S.. The Journal of Neuroinflammation is the most authoritative choice for researchers. The main research focuses in this field include multiple sclerosis, Parkinson’s disease, blood-brain barrier, COVID-19, Alzheimer's disease, gene therapy. In recent years, stress have emerged as hot keywords, particularly depression, human immunodeficiency virus-associated neurocognitive disorders, blood-brain barrier, gut microbiota related directions, indicating a potential shift in research focus. Conclusions Research on the virus and neuroinflammation has attracted increasing attention in the past decade. European and American countries have been pivotal in conducting research on virus and neuroinflammation, while China has produced a significant number of publications, its impact is still limited. Stress is likely to emerge as the next area of focus in this field. The association and regulation between viral infection and psychiatric disorders are not fully understood, and further research is needed to explore the role of neuroinflammation caused by different types of viral infection and psychiatric disorders.